2009
DOI: 10.1111/j.1617-0830.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung Imaging in Cystic Fibrosis

Abstract: Summary Management of CF patients currently relies on clinical status, lung function tests, sputum cultures and scoring systems based on chest X‐ray (CXR). None of these tests give adequate information about regional lung function or are sensitive enough to demonstrate subtle changes that may aid in assessing early lung disease status, planning therapy or evaluating response to treatment. There is increasing evidence from recent studies with CT and MRI that current routine measures of lung physiology, (spirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…MRI comprising two or three sequences is helpful in reducing the false-positive rate. It was found that 3T MRI has more difficulty detecting ground glass opacities than 1.5T MRI [ 64 ]. 1.5T MRI with SSFP sequences successfully detected ground glass opacities in 75% of lung fibrosis subjects [ 65 ].…”
Section: Clinical Lung Screening Modalitiesmentioning
confidence: 99%
“…MRI comprising two or three sequences is helpful in reducing the false-positive rate. It was found that 3T MRI has more difficulty detecting ground glass opacities than 1.5T MRI [ 64 ]. 1.5T MRI with SSFP sequences successfully detected ground glass opacities in 75% of lung fibrosis subjects [ 65 ].…”
Section: Clinical Lung Screening Modalitiesmentioning
confidence: 99%
“…The authors investigated T1-weighted and T2-weighted MRI to detect small lung nodules [ 30 , 31 ]. Compared to 3T 1.5 MRI, 1.5T MRI is much easier to identify ground glass opacities [ 32 ]. Ground glass opacities were successfully detected in 75% of subjects with lung fibrosis who received 1.5T MRI with SSFP sequences [ 33 ].…”
Section: Lung Imaging Techniquesmentioning
confidence: 99%